Pengaruh Motivasi Orang Tua Terhadap Minat Belajar Siswa Kelas IV SDI Boanawa 1 Kecamatan Ende Selatan Kabupaten Ende - Benedikta Boleng (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this study was to determine whether or not there was an influence of parental motivation on students' interest in learning at SDI Boanawa 1, Ende Selatan District, Ende Regency. The type of research is correlative quantitative research. The population of this research was the students of SDI Boanawa with the samples being class IVA and IVB which amount to 38 students. The research technique carried out was by distributing questionnaires and documentation. The data analysis technique used is statistics with the help of SPSS 23.0 software. The results shows that the regression equation Y = 1.346 + 0.863 X. Based on the hypothesis testing obtained tcount = 3.118 and ttable = 2.014, a decision was taken that H0 was rejected because tcount >ttable  means that there is a significant influence between parents 'motivation on SDI students' learning interest at SDI Boanawa 1. So the regression equation can be used to predict or predict the size of the criterion variable (Y) based on the predictor variable (X). And obtained R Square = 0.990, this value implies that the influence of parents' motivation on learning interest is 99% and 1% is determined by other variables.